Antitumoral Effect of Plocabulin in High Grade Serous Ovarian Carcinoma Cell Line Models - Heredia-Soto, Victoria; Escudero, Javier; Miguel, María; Ruiz, Patricia; Gallego, Alejandro; Berjón, Alberto; Hernández, Alicia; Martínez-Díez, Marta; Zheng, Shuyu; Tang, Jing; Hardisson, David; Feliu, Jaime; et al. (Frontiers in Oncology, 2022)
Ovarian cancer (OC) is a life threatening tumor and the deadliest among gynecological cancers in developed countries. First line treatment with a carboplatin/paclitaxel regime is initially effective in the majority of patients, but most advanced OC will recur and develop drug resistance. Therefore, the identification of alternative therapies is needed. In this study, we employed a panel of high-grade serous ovarian cancer (HGSOC) cell lines, in monolayer and three-dimensional cell cultures. We evaluated the effects of a novel tubulin-binding agent, plocabulin, on proliferation, cell cycle, migration and invasion. We have also tested combinations of plocabulin with several drugs currently used in OC in clinical practice. Our results show a potent antitumor activity of plocabulin, inhibiting proliferation, disrupting microtubule network, and decreasing their migration and invasion capabilities. We did not observe any synergistic combination of plocabulin with cisplatin, doxorubicin, gemcitabine or trabectedin. In conclusion, plocabulin has a potent antitumoral effect in HGSOC cell lines that warrants further clinical investigation.